Late Woodland settlement ecology of the Appalachian Summit. Issue 1 (2nd January 2022) - Quinn, Colin P.; Walker, Emily; Wright, Alice
ABSTRACT: The Late Woodland (ca. AD 800–1500) was a time of socioeconomic and environmental change in the Appalachian Summit. Changing climatic conditions and the introduction of maize agriculture made permanent settlement in these high-elevation mountain landscapes possible for the first time. We adopt a settlement ecology approach to examine how Late Woodland communities situated themselves in the landscape. Drawing upon geospatial analyses of legacy datasets, we document how Late Woodland communities prioritized access to different socioeconomic resources in the New River Headwaters region of northwest North Carolina. The New River Headwaters was an important source of natural resources, including mica and copper, as well as an important corridor for the movement of people and resources throughout Eastern North America. Our analyses demonstrate that Late Woodland communities balanced access to arable land, copper sources, and long-distance trade routes when situating their settlements. Larger sites had access to more land suited for maize agriculture than smaller sites. The largest sites in the region were also well-positioned with nearby access to copper sources and trade routes along the New River. Regional approaches to Late Woodland occupation in the Appalachian Summit reveal the dynamic relationship between humans and the environment in mountain landscapes.